Comparison of the spectroscopically measure catalyst transformation and electrochemical properties of Grubbs' first- and second-generation catalysts - Swart, Marthinus R.; Marais, Charlene; Erasmus, Elizabeth (American Chemical Society, 2021)
According to UV–vis spectroscopy (0.10 mM, CH2Cl2 at 25 °C), the catalyst transformation (which could possibly include ligand dissociation with active catalyst formation, dimer formation, and decomposition) rate constants (kobs) of Grubbs’ first (1) and second (2) generation catalysts are 7.48 × 10–5 and 1.52 × 10–4 s–1, respectively. From 31P NMR (0.1 M, CD2Cl2, at 25 °C), the catalyst transformation was 5.1% for 1 and 16.5% for 2 after 72 h. However, due to the larger concentrations of the NMR samples compared to the UV–vis samples, the extent of transformation did not correspond. The oxidation potential of the RuII/RuIII couple of 2 (E°’ = 27.5 mV at v = 200 mV s–1) was considerably lower than that of 1 (E°’ = 167 mV at v = 200 mV s–1). In the case of 1, a second reduction peak appeared at slow scan rates. This may probably be ascribed to an electrochemically active compound that was formed from the intermediate cation 1•+ and the subsequent reduction of the latter. The oxidation/reduction of 1 proceeds according to an ErCi electrochemical mechanism (Er = electrochemically reversible step, Ci = chemically irreversible step), whereas 2 proceeds according to an ErCr electrochemical mechanism (Er = electrochemically reversible step, Ci = chemically reversible step).
Keywords: Electrochemistry; Grubbs; Transformation